Accurate Preoperative Diagnosis of Ovarian Pregnancy with Transvaginal Scan - Natasha Gupta; Anu Gupta; Godwin Onyema; Yelena Pantofel; Shan-Ching Ying; Jack E. Garon; Charles Lampley; Josef Blankstein (Hindawi Limited, 2012)
Ovarian pregnancy is a rare variant of ectopic pregnancy, and an accurate preoperative diagnosis is very challenging. Dr. Saint Monnissey described the first reported case of ovarian pregnancy in 17th century. Transvaginal ultrasonography is a valuable tool in identifying an ovarian pregnancy from other types of ectopic pregnancies. Management with laparoscopy or laparotomy is required in all cases, and in almost all cases, ovary can be preserved since implantation is usually superficial (Koo et al.; 2011). A single case of an ovarian pregnancy, consistent with Spiegelberg's criteria is presented here. This case history demonstrates the use of ultrasonography (USG) and surgery in the diagnosis and treatment, respectively, of the ovarian pregnancy. As we step into an era where in vitro fertilization rate is on its hike, one should be aware that incidence of ovarian pregnancy is also increasing, necessitating a high index of suspicion.